2005
DOI: 10.1007/s11373-004-8177-5
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 increases hypoxia-inducible factor-1 and vascular endothelial growth factor to promote angiogenesis in gastric carcinoma

Abstract: Cyclooxygenase-2 (COX-2) is an inducible enzyme important in inflammation and which is overexpressed in a variety of cancers. This study investigated its role in angiogenesis of gastric carcinoma (GC). Immunohistochemical examination of surgical specimens showed a positive correlation among COX-2, vascular endothelial growth factor (VEGF), and vasculature in GC. After transfection with a COX-2-expressing vector, the AGS GC cell line showed increases in both proliferation and tube formation of human umbilical v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 41 publications
4
79
0
1
Order By: Relevance
“…Reactive oxygen species regulate HIF stability and transcriptional activity under hypoxia and normoxia (Pouyssegur and Mechta-Grigoriou, 2006). Inflammation-mediated COX-2 expression is an early feature of Barrett's carcinogenesis (Morris et al, 2001) and, in a gastric cancer model, the COX-2/PGE2/HIF-1/VEGF pathway was shown to contribute to tumour angiogenesis (Huang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species regulate HIF stability and transcriptional activity under hypoxia and normoxia (Pouyssegur and Mechta-Grigoriou, 2006). Inflammation-mediated COX-2 expression is an early feature of Barrett's carcinogenesis (Morris et al, 2001) and, in a gastric cancer model, the COX-2/PGE2/HIF-1/VEGF pathway was shown to contribute to tumour angiogenesis (Huang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of HIF-1α function results in the reduction of VEGF secretion in vitro, and in the inhibition of tumor growth and angiogenesis in vivo [31]. VEGF and HIF-1α are upregulated by cyclooxygenase-2 (COX-2) overexpression through a prostaglandin E2 (PGE2)-dependent pathway [32]. We found here that the increased expression of HIF-1α and VEGF had no association with the clinicopathological findings on prognosis, except for the rare occurrence of distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show that VEGF and HIF-1· accelerate angiogenesis by upregulating HO-1 in endothelial cells (17,28,29). However, it is unclear whether HO-1 is associated with angiogenesis and other angiogenic factors in UC of the bladder.…”
Section: Introductionmentioning
confidence: 99%